Effects of Protein Levels and Supplementation of Methyl Group Donor on Nutrient Digestibility and Performance of Broiler Chickens in the Tropics - Ratriyanto , Adi; Indreswari, Rysca; Sunarto (International Journal of Poultry Science, 2014)
This study was conducted to investigate the effects of protein levels and supplementation of methyl group donors on nutrient digestibility and performance of broiler chickens. Three experimental diets were formulated to have three levels of crude protein (23, 21.5 and 20%). Each protein level was supplemented with methyl group donor (methionine or betaine) and was categorized by: without supplementation (control), with supplementation of 0.14% methionine, 0.14% betaine and combination of 0.14% methionine plus 0.14% betaine. The diets were applied to 540 broiler chickens, which were randomly assigned to 3 x 4 factorial arrangement. Dietary with 21.5 and 20% protein and the supplementation of methyl group donor increased the digestibility of dry matter, crude protein and crude fiber (p<0.05). Dietary with 23 and 21.5% protein resulted in a higher daily gain and a lower abdominal fat compared to that with 20% protein (p<0.05). All methyl group donor supplementations increased carcass and breast yield, while only supplementation with betaine and methionine plus betaine decreased abdominal fat deposition (p<0.05). Therefore, it is concluded that dietary with 21.5% protein can be applied to broiler chickens. Supplementation of methyl group donor provided benefits, particularly to improve carcass characteristics of broilers.